Outcomes of processing of bone marrow harvests for hematopoietic stem cell transplantation in pediatric patients utilizing a novel red blood cell sedimentation kit. Issue 7 (8th May 2019) - Akel, Salem; Murray, Christianna; Ferguson, William; Babic, Aleksandar
Abstract : BACKGROUND: Bone marrow (BM) grafts are often subject to manipulation to minimize infusion volume, to deplete red blood cells (RBCs), to deplete plasma, and/or to achieve optimal concentration of nucleated cells (NCs) for freezing. Here, we report results of processing and infusion of four major ABO‐incompatible BM grafts for allogeneic hematopoietic transplantation in pediatric patients. CASES AND METHODS: Patients ranging in age from 5 months to 18 years received hematopoietic stem cell transplantation for benign or malignant indications. Allogeneic BM grafts were processed using PrepaCyte‐CB kits, approved by the Food and Drug Administration for enrichment of mononuclear cells in cord blood units for hematopoietic transplantation. Resulting grafts were dosed and infused using standard institutional protocol. After transplantation patients were evaluated for hematologic recovery. RESULTS: The PrepaCyte‐CB processing method achieved on average 97.1% depletion of RBCs and 68.5% volume reduction, with a fairly efficient NC recovery (total NCs, 85.6%; white blood cells, 89.7%; CD34+ cells, 103.3%; and colony‐forming unit cells, 87.5%). No microbial contamination was detectable in any of the processed grafts. Infusions were well tolerated, and all four patients achieved durable hematopoietic engraftment within expected time interval. CONCLUSION: Our results suggest that PrepaCyte‐CB is safe and effective for minimal processing of BM grafts. Engraftment outcomes were comparable with other published BM processing methods. In addition, NC recovery achieved using this method appears to exceed that of previously described sedimentation reagents such as hetastarch and Ficoll.